Amino/alkoxycarbonylation of aryl halides mediated by group VI metal carbonyl complexes - Ren, Wei (2012)
A novel simple process of group VI metal carbonyl complex-mediated carbamoylation and alkoxycarbonylation of organic halides are described. Caboxylic amides are easily prepared by carbamoylation of aryl halides which was accomplished in the reaction of aryl halides and amines in the presence of group VI metal carbonyl complex such as Mo(CO)6. In this reaction, the metal carbonyl complex acts as the catalyst and source of carbon monoxide. The conventional amide formation, palladium-catalyzed three component coupling, only proceeds under gaseous carbon monoxide, therefore, it requires a large excess use of carbon monoxide. On the other hand, the developed carbamoylation requires only slight excess to the stoichiometric amount of carbon monoxide in the form of metal carbonyl complex. The methodology is also applicable for the preparation of esters in the alkoxycarbonylation of aryl halides with alcohols instead of amines. Finally, this method was applied to synthesize heterocyclic compounds such as benzoxazones.